(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this paper, experimental has been executed to investigate thermal performance of modified design of mini-channel plate solar collector. For the application of mini-channel heat exchangers, it is necessary to have perfect design tools for prophesy pressure drop and heat transfer. Experimental setup were carried out in Baghdad city from (July) with a tilt angle of (30º) to the south under sunny weather condition. The working fluid is propylene glycol in the laminar regime is used for experimental investigation at constant fluid inlet temperature (15 ºC - 20 ºC) and at different flow rates (4.6L/h, 5.77L/h, 7.96L/h, 11.2L/h, and 18.35L/h). The mini- channel solar collector performance is evaluated in terms of heat transfer coefficient, pressure drop, friction factor pumping power, and working fluid temperature difference between the outlet and the inlet .In this paper study the test rig with selective coating and with cover glass The experimental results show that an increase in mass flow rate the heat transfer coefficient is also increased while the friction factor is decreased. Also, increase in mass flow rate lead to the temperature difference between the outlet and the inlet working fluid decreases.